Dampak Fasilitas Dan Niat Menggunakan Terhadap Perilaku Pengguna E-Learning - Rahman, M Fathur; Murniawaty, Indri (Universitas Negeri Semarang, 2021)
The purpose of this study was to analyze the effect of facility conditions, intention to use and user behavior. This study uses an explanatory quantitative approach with a sample of 280 respondents. Methods of data collection using the method of documentation and questionnaires. The data analysis method uses SEM with the WarpPLS approach which will test causality in the exploratory design, so that a causal path of new findings is obtained that is more suitable for use in interpreting the data correctly and accurately. The results of this study indicate that the condition of adequate facilities can increase the behavioral intentions and interests of e-learning users.